COMPUTER SIMULATION OF PHASE TRANSITIONS IN THE TWODIMENSIONAL STRUCTURES DESCRIBED THREE-VERTEX ANTIFERROMAGNETIC POTTS MODE ON A TRIANGULAR LATTICE - A. B. Babaev; G. A. Dibirova; M. B. Saidakhmedova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Using Monte-Carlo simulations, we investigated phase transitions and frustrations in the three-state Potts model on a triangular lattice with allowance for antiferromagnetic exchange interactions between nearest- neighbors J1 and next- nearest- neighbors J2. The ratio of the next-nearest- neighbor and nearest- neighbor exchange constants r=J2/J1 is chosen within the 0÷2 range. Based on the analysis of the entropy, specific heat, system state density function, and fourth order Binder cumulants, the phase transitions in the Potts model with interactions J1<0 and J2<0 are shown to be found in value ranges of 0 r<0.2 and 1.0<r 2.0. In an intermediate range 0.2 r 1.0 the phase transition fails and the frustrations are revealed.